The Potential Cytotoxic Activity Enhancement of α-Mangostin in Chitosan-Kappa Carrageenan-Loaded Nanoparticle against MCF-7 Cell Line - Wathoni, Nasrul (Polymers (Basel), 2021)
α-mangostin (αM), a xanthone derivative compound isolated from the extract of mangosteen pericarp (Garcinia mangostana L), has potential anticancer properties for breast cancer. However, it has poor solubility in water and low selectivity towards cancer cells. The polymeric nanoparticle formulation approach can be used to overcome these problems. In this study, a chitosan biopolymer-based αM polymeric nanoparticle formulation was encapsulated using kappa carrageenan (αM-Ch/Cr) as a novel carrier for breast cancer therapy and evaluated for their physicochemical properties, drug release profile, and in vitro cytotoxicity against breast cancer cells (MCF-7). Polymeric nanoparticles formulated with varying concentrations of kappa carrageenan were successfully prepared by ionic gelation and spray pyrolysis techniques. αM-Ch/Cr nanoparticles formed perfectly round particles with a size of 200–400 nm and entrapment efficiency ≥ 98%. In vitro release studies confirmed that αM-Ch/Cr nanoparticles had a sustained release system profile. Interestingly, the formulation of polymeric nanoparticles significantly (p < 0.05) increased the cytotoxicity of αM against MCF-7 cell with IC50 value of 4.7 μg/mL compared to the non-nanoparticle with IC50 of 8.2 μg/mL. These results indicate that αM-Ch/Cr nanoparticles have the potential to improve the physicochemical properties and cytotoxicity effects of αM compounds as breast cancer therapy agents.